Дослідження лідерських якостей у студентів технічних університетів: результати експерименту - Ріпко, Ірина Валентинівна (Класичний приватний університет, 2015)
У статті розглянуто проблему підвищення розвитку лідерських якостей майбутніх інженерів у процесі професійної підготовки в технічних університетах на підставі аналізу результатів констатувального експерименту. На прикладі дослідження лідерських якостей у групі аспірантів НТУ "ХПІ" актуалізовано необхідність формування лідерського потенціалу в студентів технічних університетів. На підставі даних експерименту визначено групу лідерських якостей, які респонденти вважають найбільш значущими для свого майбутнього. Вказано, що педагогічну діагностику проведено відповідно до акмеологічного підходу.

The article deals with the problem of increasing the development of leadership qualities of future engineers in the process of professional preparation in technical universities on the basis of analysis of the pedagogical ascertaining experiment. Through case studies leadership in a group of graduate students at National Technical University "Kharkov Polytechnic Institute" actualized the necessity of forming leadership capacity in students of technical universities. The article states that in the experiment were investigated following leadership qualities: organizational skills, communication skills, ambition, efficiency, creative qualities of the personality, diligence, initiative, perseverance, responsibility, innovative thinking, dedication, determination, ethical conduct, technical (vocational) competence motivation to achieve success, risk tolerance (adventurism), the ability to influence subordinates. On the basis of experimental data in this paper the group leadership qualities that are considered most important by the respondents for their future. These are the following leadership qualities: responsibility, diligence, communication skills, innovative thinking, ambition, technical (vocational) competence, perseverance, determination, commitment, efficiency, a high level of etiquette, increasing both technical and cultural standards, the rapid assimilation of knowledge and skills. The article states that the conduct of pedagogical diagnostics was based on compliance with the requirements the conditions acmeologic approach, so the data presented will be of interest not only for the teachers involved in the education of students at technical universities, but also for other professionals involved in the formation of leadership qualities.
The Study of Leadership Qualities in Students of Technical Universities: the Results of the Experiment
Keywords: лідерські якості; лідерський потенціал; професійна підготовка; студенти технічних університетів; експеримент; leadership qualities; leadership potential; students of technical university; experiment